New-instutionalism and the origins of the African Union - Bizos, Anthony (My University, 2011)
The inauguration of the African Union (AU) in July 2002 represents an ambitious project to establish frameworks and institutions that promote regional integration and co-operation to address the continent’s perils. This is particularly true in the security and defence sectors. Because conflicts in Africa have been characterised by humanitarian catastrophes, regional co-operation now reflects the priorities of human security and development. In particular, the Constitutive Act of the AU enforces the principles of the responsibility to protect (R2P) the right to intervene in a member state in respect of grave circumstances and intolerance of unconstitutional changes of government. At first glance these principles seem contrary to international law, the notion of sovereignty and the primacy of the UN Security Council in matters of international peace and security. Using new- institutionalism approaches the research will examine the process whereby the AU originated and how the organisation affects member state behaviour. In particular, the research will examine whether one can identify a critical juncture to account for the origins of the AU and whether the norms enshrined in its Constitutive Act are being internalised by member states. It is the contention of the research that calculations of material interest and power balancing often compete with norm localisation thus affecting institutional predictability and the ability of the African Union to fulfil its mandate